Analysis of Leadership Crisis Factors in Islamic Educational Institutions (Case Study at MAS Al-Washliyah Tanjung Tiram) - Cahaya, Cahaya; Rusdi, Muhammad; Damanik, Muhammad Zein (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2024)
MAS Al-Washliyah Tanjung Tiram as one of the long-established Islamic educational institutions in Batu Bara Regency faces serious challenges related to the effectiveness and quality of leadership in the school. The leadership crisis at MAS Al-Washliyah Tanjung Tiram is the result of a complex interaction between internal and external factors. To overcome this crisis, strategic steps are needed that involve improving leadership competencies, strengthening communication, and adapting to external changes. The purpose of this article is to describe and analyze the internal and external factors that caused the leadership crisis at MAS Al-Washliyah Tanjung Tiram, Batu Bara Regency. This research uses a type of qualitative research with a case study approach. Data were collected through in-depth interviews, participative observation, and document analysis. The results showed that the internal factors that caused the leadership crisis at MAS Al-Washliyah Tanjung Tiram Batu Bara Regency included ineffective communication, lack of innovation and adaptation, problems in resource management, and lack of support and staff development. Meanwhile, from an external aspect, the causes of the leadership crisis at MAS Al-Washliyah Tanjung Tiram Batu Bara District are changes in government policy, economic pressure, competition with other educational institutions, and technological developments.